2020
DOI: 10.1080/02670844.2020.1792206
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plasma nitriding at low temperature on the corrosion resistance and conductivity of 2205 duplex stainless steel

Abstract: A nitrogen expanded austenite (γ N ) layer with a thickness of 3 μm was prepared by plasma nitriding of 2205 duplex stainless steel (DSS) at 460°C for 1 h with hollow cathode discharge assistance. The microstructure and phase composition of nitrided specimens were examined. The electrical conductivity of nitrided samples was measured before and after the corrosion test, respectively. The corrosion current density of nitrided 2205 DSS polarized for 4 h was 1.3 μA cm −2 (at 0.6 V) and −1.4 μA cm −2 (at −0.1 V), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…It is reported in the literature that an increase in the corrosion potential and a decrease in the corrosion current, with respect to the untreated sample, are parameters that indicate that a material has improved its corrosion resistance [19], [20], [21]. As shown in Table 1, two coatings meet both premises, the 5 s and the 120s.…”
Section: O-h C-cmentioning
confidence: 86%
“…It is reported in the literature that an increase in the corrosion potential and a decrease in the corrosion current, with respect to the untreated sample, are parameters that indicate that a material has improved its corrosion resistance [19], [20], [21]. As shown in Table 1, two coatings meet both premises, the 5 s and the 120s.…”
Section: O-h C-cmentioning
confidence: 86%
“…An equal 3-electrode cell apparatus and stabilization period was employed in the potentiodynamic polarization tests. Starting from −30 mV below the OCP, the potential was swept at a scanning rate of 1 mV s −1 [16][17][18][19]. Potentiodynamic tests were performed in triplicates.…”
Section: Methodsmentioning
confidence: 99%
“…Nitriding treatment is driven by the concentration gradient, nitrogen atoms gradually are diffused into the material to achieve the purpose of nitriding, and there is no interface adhesion problem between the nitriding layer and the matrix. The plasma nitriding technology is the best way to improve the surface properties of the stainless steel because it has the advantages of mass production, no pollution and low cost [13,14]. The previous research results indicated that the plasma nitriding treatment can significantly enhance the conductivity and corrosion resistance of metals [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%